Implementation of BIPA Learning at Muhammadiyah University of Kendari: Obstacles and Solutions - Ikbal, Laode; Maulina, Maulina; Faridawati, Faridawati (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2026)
The internal difficulties of Muhammadiyah University Kendari's BIPA program are examined in this descriptive qualitative study using case studies. The results point to three primary barriers: pedagogical proficiency and instructional materials, students' language skills (pronunciation and structuring), cultural adjustment, and facility limitations. To solve these challenges, educators, staff, and students can employ solution ideas to create implementative plans and tactical actions. This study develops strategic recommendations to enhance the program's efficacy through rigorous triangulation, document analysis, interviews, and participatory observation. This strengthening is essential as a tool of cultural diplomacy in the global arena to develop a creative, relevant, and adaptable learning ecosystem for international learners in the digital era, in addition to boosting the quality of education.